Mirror-finished duplex stainless steel with excellent image clarity and scratch resistance and its manufacturing method

JP7645115B2Active Publication Date: 2025-03-13NIPPON STEEL CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021054343
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-03-13
Estimated Expiration
2041-03-26

AI Technical Summary

Benefits of technology

【0009】 本発明の一態様によれば、写像性および耐疵付き性に優れる鏡面仕上げ複相ステンレス鋼を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645115000003
    Figure 0007645115000003
  • Figure 0007645115000004
    Figure 0007645115000004
  • Figure 0007645115000005
    Figure 0007645115000005
Patent Text Reader

Abstract

To provide a mirror finished dual-phase stainless steel which is excellent in image clarity and scratch resistance, and a method for producing the same.SOLUTION: A stainless steel contains, by mass%, 0.01-0.2% of C, 0.01-2.0% of Si, 0.1-4.0% of Mn, 0.05% or less of P, 0.03% or less of S, 10-20% of Cr, 0.01-4.0% of Ni, 0.15% or less of N, and 0.01% or less of O, includes a ferrite phase and a martensite phase, and has a hardness of 200-350 HV, a waviness of 2.0 μm or less, and an arithmetic average surface roughness (Ra) of 0.1 μm or less, and in an arbitrary cross section, an area ratio of the martensite phase is 60-80%, an area ratio of a carbide is 0.5-2.0%, and a major axis of each of the carbides is 1 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mirror-finished duplex stainless steel and a method for producing the same. [Background technology]

[0002] Austenitic stainless steel has traditionally been used as a metal material for mirrors, but conventional austenitic mirror-finished stainless steel is soft, generally with a surface hardness of HV200 or less, making it prone to scratches.

[0003] Therefore, Patent Document 1 proposes mirror-finished stainless steel that is less susceptible to scratches and cracks and can be made lighter by increasing strength through mirror polishing of high-strength duplex structure stainless steel. Patent Document 1 describes a mirror-finished duplex stainless steel sheet that has a mixed structure of ferrite and martensite, a hardness of HV330 or more, and a mirror gloss of Gs(20°)=1200-1300. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-152550 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the duplex stainless steel sheet described in Patent Document 1 has high hardness, which increases deformation resistance, making it difficult to obtain sufficient flatness through straightening, and may result in reduced image clarity after mirror polishing.

[0006] An object of one aspect of the present invention is to provide a mirror-finished duplex stainless steel that has high strength and excellent image clarity and scratch resistance. [Means for solving the problem]

[0007] In order to solve the above problems, a mirror-finished duplex stainless steel according to one embodiment of the present invention has a composition, by mass%, of 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.15% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities, and contains a ferrite phase and a martensite phase, has a hardness of 200 to 350 HV, a waviness of 2.0 μm or less, and a surface arithmetic mean roughness (Ra) of 0.1 μm or less, and in any cross section, the area ratio of the martensite phase is 60 to 80%, the area ratio of carbides is 0.5 to 2.0%, and the major axis of each of the carbides is 1 μm or less.

[0008] Furthermore, a method for producing a mirror-finished duplex stainless steel according to one embodiment of the present invention includes a final annealing step in which the steel is heated to a temperature range of 800 to 1100°C after a cold rolling step, and then soaked in the temperature range for less than 1 minute, and then cooled at a cooling rate of 1°C / s or more; a straightening step by repeated tensile bending back processing; and a mirror polishing step. The mirror-finished duplex stainless steel has a composition, by mass%, of 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.15% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities. Effect of the Invention

[0009] According to one aspect of the present invention, a mirror-finished duplex stainless steel having excellent image clarity and scratch resistance can be realized. [Brief description of the drawings]

[0010] [Figure 1] 1 is a SEM photograph of an arbitrary cross section of a duplex stainless steel according to an embodiment of the present invention. [Diagram 2] 1 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the hardness of duplex stainless steel. [Diagram 3] 1 is a graph showing the influence of the holding time at the duplexing temperature and the duplexing temperature on the martensite area ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An embodiment of the present invention will be described in detail below. The following description is for better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified. In this specification, "A to B" indicates A or more and B or less. In this specification, "%" regarding chemical composition means "mass %" unless otherwise specified.

[0012] <Terminology> The term "stainless steel" refers to a stainless steel material not limited to a specific shape, and examples of the stainless steel material include steel plates, steel pipes, and bar bars.

[0013] As used herein, unless otherwise specified, "duplex stainless steel" means a stainless steel containing ferritic and martensite phases.

[0014] <General manufacturing method> First, an example of a general manufacturing process for stainless steel strip will be described in outline. In one example, the general manufacturing process for stainless steel strip includes a steelmaking process, a hot rolling process, an annealing process, a pickling process, a cold rolling process, an annealing and pickling process, and a finish rolling process in this order. Each of these steps in the conventional manufacturing process is publicly known, and therefore detailed description thereof will be omitted except for the following description.

[0015] The following describes the characteristics of the mirror-finished duplex stainless steel according to one embodiment of the present invention. In the following description, if the characteristics are the same whether it is a duplex stainless steel after the final annealing process (before mirror finishing) or a duplex stainless steel after a mirror polishing process, they will be described simply as the characteristics of "duplex stainless steel". However, it should be noted that the mirror-finished duplex stainless steel also has the same characteristics.

[0016] <Summary of the Invention and Findings> Duplex stainless steel has a duplex metal structure consisting of a relatively soft and ductile ferrite phase and a strong martensite phase. Therefore, duplex stainless steel is known as a stainless steel that has both strength and ductility. However, when the duplex stainless steel has a high hardness (e.g., greater than 350 HV), the deformation resistance is high, and sufficient flatness may not be obtained in the straightening process, which is one of the processes for obtaining mirror-finished stainless steel. In addition, the polishing load is high in the mirror polishing process, and the consumption of grinding wheels increases.

[0017] In order to reduce the deformation resistance and improve the polishability, it is conceivable to soften the duplex stainless steel by reducing the phase ratio of the martensite phase in the duplex stainless steel. However, when the phase ratio of the martensite phase is reduced, the phase ratio of the martensite phase that ensures the strength is reduced, and the strength of the duplex stainless steel itself is also reduced.

[0018] On the other hand, if the hardness of the duplex stainless steel is too low, there arises a problem that it is easily scratched.

[0019] As a result of intensive research, the inventors have found that mirror-finished duplex stainless steel with high strength, excellent image clarity, and scratch resistance can be obtained by shortening the holding time in the duplex temperature range in the duplex heat treatment and then performing the straightening process and mirror polishing process (see the examples described later). The mirror-finished duplex stainless steel in this embodiment has high strength and can reduce the weight of the final product because the phase ratio of the martensite phase is maintained at a high rate. In addition, the duplex stainless steel in this embodiment has a hardness (Vickers hardness) of 200 to 350 HV, so it has excellent deformation workability and scratch resistance.

[0020] Due to its excellent deformation workability, sufficient flatness can be obtained in the straightening process described in detail below, and a mirror-finished duplex stainless steel with excellent image clarity can be obtained. In addition, since the hardness is about 200 to 350 HV, it has the advantage of being less subject to polishing compared to conventional ferritic-martensite duplex stainless steels.

[0021] That is, according to one embodiment of the present invention, it is possible to provide a mirror-finished duplex stainless steel having high strength and excellent image clarity. In addition, the mirror-finished duplex stainless steel can be manufactured while reducing the possibility of an increase in manufacturing costs.

[0022] <Duplex stainless steel of the present invention> FIG. 1 is a SEM photograph of a cross section of a duplex stainless steel according to an embodiment of the present invention. As shown in FIG. 1, in a cross section of a duplex stainless steel according to an embodiment of the present invention, carbides can be observed as granular matter dispersed within the material. Examples of carbides present in the duplex stainless steel include (Fe, Cr) 23C6, etc. The area ratio of carbide is the ratio of the area where carbide exists (total area of ​​carbide particles) in a given area of ​​the cross section of the duplex stainless steel. The long diameter of carbide means the longest diameter among the diameters of particulate carbide. In the duplex stainless steel according to one embodiment of the present invention, the long diameter of each carbide confirmed in the cross section of the duplex stainless steel is 1 μm or less. The direction of the cross section of the duplex stainless steel when measuring the area ratio of martensite phase and carbide, and the long diameter of carbide is not particularly limited. For example, the cross section may be parallel to the rolling direction and plate thickness direction of the duplex stainless steel.

[0023] The duplex stainless steel according to the present embodiment has both ductility and strength by including a ferrite phase having ductility and a martensite phase having strength. The higher the ratio of the hard martensite phase, the higher the strength of the duplex stainless steel itself. However, if the ratio of the martensite phase is excessively high, the ductility of the duplex stainless steel decreases, making processing difficult. Therefore, the duplex stainless steel according to the present embodiment has an area ratio of the martensite phase in any cross section of the duplex stainless steel of 60 to 80%. This ensures the strength of the duplex stainless steel itself.

[0024] When duplex stainless steel is subjected to deformation processing, if the hardness of the duplex stainless steel is high, the workability decreases. On the other hand, if the hardness of the duplex stainless steel is too low, defects are likely to occur when the product is mirror-finished. Therefore, the hardness of the duplex stainless steel in this embodiment is 200 to 350 HV.

[0025] In duplex stainless steels having the same composition, the difference in the area ratio of carbides in a cross section is considered to be due to the difference in the amount of C dissolved in the martensite phase. That is, in duplex stainless steels having the same composition, the lower the area ratio of carbides, the greater the amount of C dissolved in the martensite phase. If the amount of C dissolved in the martensite phase is large, the hardness of the martensite phase increases, which causes the hardness of the duplex stainless steel itself to increase, adversely affecting the deformation workability. Therefore, in the duplex stainless steels having the composition of the present invention, the preferred area ratio of carbides in any cross section of the duplex stainless steel is 0.5 to 2.0%.

[0026] Furthermore, in the duplex stainless steel, if the carbides are coarse, defects due to the carbides may occur. Therefore, in the duplex stainless steel according to the present embodiment, the major axis of each carbide in any cross section is 1 μm or less, more preferably 0.75 μm or less. This can improve the deformation workability of the duplex stainless steel.

[0027] (composition) The duplex stainless steel according to this embodiment contains, as essential components, in mass%, 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.15% or less N, and 0.01% or less O, with the balance being Fe and unavoidable impurities.

[0028] In addition, the duplex stainless steel according to this embodiment may contain at least one of the following optional components: 4.0% or less Cu, 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM (rare earth elements). The significance of the content of each element contained in the duplex stainless steel according to this embodiment will be described below.

[0029] C is an austenite-forming element that facilitates the formation of the austenite phase. C stabilizes the austenite structure and improves the strength of martensite formed during annealing and / or cooling. When the C content is high, C increases the volume fraction of the martensite phase and dissolves in the martensite, improving the strength of the stainless steel. Therefore, C is an important element for ensuring the strength of stainless steel. However, if the C content of stainless steel is too high, the deformation resistance becomes too high and image clarity decreases. In addition, if the C content of stainless steel is too high, toughness and corrosion resistance decrease. Therefore, the duplex stainless steel according to this embodiment contains 0.01 to 0.2% C.

[0030] Although Si is an element that has a deoxidizing effect on stainless steel, it is also a ferrite phase forming element that makes it easier to form ferrite phase, so if the Si content is high, a sufficient amount of martensite (volume ratio of martensite phase) cannot be obtained. On the other hand, excessively low Si content in stainless steel leads to increased refining costs. Therefore, the duplex stainless steel according to this embodiment contains 0.01 to 2.0% Si.

[0031] Mn is an austenite-forming element and is effective for obtaining a martensite phase. However, a large amount of Mn content leads to an increase in deformation resistance because the volume fraction of the martensite phase becomes too high. Therefore, the duplex stainless steel according to this embodiment contains 0.1 to 4.0% Mn.

[0032] P and S are unavoidable impurities. Since P and S are elements that reduce toughness, in the duplex stainless steel according to this embodiment, the P content is 0.05% or less and the S content is 0.03% or less.

[0033] Cr is an effective component for improving the corrosion resistance of stainless steel. However, since Cr is a ferrite forming element that facilitates the formation of ferrite phase, if the Cr content of stainless steel becomes too high, the volume fraction of the martensite phase decreases. Therefore, the duplex stainless steel according to this embodiment contains 10.0 to 20.0% Cr.

[0034] Ni is an austenite-forming element and is effective in forming a martensite phase. It is also effective in improving the toughness and corrosion resistance of stainless steel. However, if the Ni content is too high, the stainless steel will be composed of only the martensite phase, and a multi-phase structure will not be obtained. Therefore, the multi-phase stainless steel according to this embodiment has a Ni content of 0.01 to 4.0%.

[0035] N is an element that increases the volume fraction of the martensite phase and contributes to improving the strength of stainless steel. N also improves the strength of stainless steel by dissolving in martensite. However, when the N content is high, the effects of phase ratio control and solid solution strengthening are saturated due to the solubility of N in austenite. Therefore, the duplex stainless steel according to this embodiment has an N content of 0.15% or less, and more preferably has an N content of 0.050% or less.

[0036] O is an unavoidable impurity. O forms oxide-based inclusions and is a factor in reducing bendability, so the O content in the duplex stainless steel according to this embodiment is 0.01% or less.

[0037] (Other Ingredients) The duplex stainless steel according to this embodiment may selectively contain one or more elements selected from the following element group in addition to the above essential components.

[0038] Cu is an austenite-forming element and is also effective for maintaining the austenite phase. If Cu is added in excess, the volume fraction of the martensite phase becomes too high, which increases the deformation resistance. Therefore, in the duplex stainless steel according to this embodiment, 4.0% or less of Cu may be added as necessary.

[0039] Mo, W, and Co are elements that improve the corrosion resistance of stainless steel. However, if the stainless steel contains excessive amounts of these elements, it becomes hard, its toughness decreases, and the material cost increases. Therefore, in the duplex stainless steel according to this embodiment, one or more of 1.0% or less Mo, 1.0% or less W, and 0.5% or less Co may be added as necessary.

[0040] Al is an effective element as a deoxidizer. However, since Al is a ferrite forming element, if excessive Al is added, it is necessary to increase the amount of austenite forming elements added. Furthermore, the effect of adding Al as a deoxidizer reaches saturation at a certain amount, and does not improve even if it is added in excess. Therefore, the duplex stainless steel according to this embodiment may contain 0.2% or less Al.

[0041] Nb, V, and Ti are elements that have a high affinity with C and N, and are precipitated as carbides or nitrides during hot rolling, which has the effect of improving high-temperature strength. On the other hand, excessive addition of these elements hardens the steel and adversely affects deformation workability. Therefore, in the duplex stainless steel according to this embodiment, one or more of 1.0% or less Nb, 1.0% or less V, and 1.0% or less Ti may be added as necessary.

[0042] B, Ca, and Mg are elements that improve hot workability and secondary workability. On the other hand, excessive addition of these elements may reduce the manufacturability of stainless steel. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.005% or less of B, 0.005% or less of Ca, and 0.005% or less of Mg may be added as necessary.

[0043] Sn and Sb are elements that improve corrosion resistance. However, excessive addition of these elements may reduce the manufacturability of stainless steel. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.5% or less of Sn and 0.5% or less of Sb may be added as necessary.

[0044] Ga and Ta are elements that improve corrosion resistance. However, excessive addition of these elements may increase the alloy cost. Therefore, in the duplex stainless steel according to the present embodiment, one or more of 0.01% or less Ga and 0.01% or less Ta may be added as necessary.

[0045] Zr, Y, Hf, and REM are elements that improve hot workability and cleanliness of steel. They are also effective as elements for improving oxidation resistance. On the other hand, excessive addition of these elements may increase alloy costs. Therefore, in the duplex stainless steel according to this embodiment, one or more of 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM may be added as necessary.

[0046] The balance of the duplex stainless steel according to this embodiment is Fe and unavoidable impurities.

[0047] <Method of manufacturing mirror-finished duplex stainless steel> An example of a method for producing a mirror-finished duplex stainless steel according to an embodiment of the present invention will be described below. The method for producing a mirror-finished duplex stainless steel according to an embodiment of the present invention is characterized in that, in the final annealing step in a general stainless steel production method, a duplex heat treatment is performed, followed by a straightening step and a mirror polishing step.

[0048] (Pretreatment process) In the pretreatment step, first, a vacuum melting furnace is used to produce steel having a composition adjusted to fall within the range of the present invention. This steel is then cast to produce a steel ingot.

[0049] (Hot rolling process) In the hot rolling process, the steel ingot after the pretreatment process is hot rolled to produce a hot rolled steel strip. The temperature in the hot rolling process may be within a general range, for example, about 800 to 1250°C.

[0050] (First annealing process) In the first annealing step, the hot rolled steel strip is annealed (batch annealing) using, for example, a batch annealing furnace (bell annealing furnace). This annealing step is referred to as the first annealing step.

[0051] (First pickling process) In the first pickling step, the annealed steel strip obtained in the first annealing step is subjected to a pickling treatment. In this first pickling step, a descaling treatment is performed on the annealed steel strip.

[0052] (Cold rolling process) In the cold rolling step, the annealed steel strip descaled in the pickling step is cold rolled at a rolling reduction of, for example, 50 to 90% to form a cold rolled steel strip.

[0053] (Final annealing process) In the manufacturing method of the duplex stainless steel according to the present embodiment, the cold-rolled steel strip cold-rolled by the cold rolling step is subjected to a duplex heat treatment as a final annealing step. Specifically, the cold-rolled steel strip is heated to a duplex temperature range of 800 to 1100°C, preferably 900 to 1000°C, and is soaked in the duplex temperature range for less than 1 minute, preferably 40 seconds or less, and then cooled at a cooling rate of 1°C / s or more, preferably 3°C / s or more. In the final annealing step, the cold-rolled steel strip is heated to a duplex temperature range of 800 to 1100°C to generate a two-phase metal structure of a ferrite phase and an austenite phase that is transformed into a martensite phase by subsequent cooling. Then, the heated cold-rolled steel strip is cooled at a cooling rate of 1°C / s or more to transform the austenite phase into a martensite phase.

[0054] In this manner, in the method for producing a duplex stainless steel according to this embodiment, a two-phase metal structure of ferrite and austenite is produced by a short period (less than 1 minute) of soaking at a temperature of 800 to 1100° C. The cooling rate from the duplex temperature range may be any rate that can transform the austenite phase into the martensite phase.

[0055] In the method for producing the duplex stainless steel according to the present embodiment, the characteristic (short) duplex heat treatment allows the production of a duplex stainless steel having the desired properties without the need for any additional heat treatment steps, and therefore the duplex heat treatment can be used as a final annealing step.

[0056] (Second pickling process, finish rolling process) If necessary, the steel strip after the final annealing step is subjected to a final pickling treatment in a second pickling step and a finish rolling step.

[0057] (straightening process) In the straightening process, the steel strip after the finish rolling process is subjected to straightening treatment, for example, by repeatedly applying tension and bending back processing using a tension leveler to improve the flatness. Since mirror-finished duplex stainless steel requires high flatness, the rolling process alone cannot satisfy the required flatness. By performing the straightening process, it is possible to improve flatness defects such as shape defects or warpage defects (e.g., waviness) remaining after the rolling process.

[0058] In this straightening process, if the hardness of the steel material subjected to the straightening process is too high, the deformation resistance is large, and there is a possibility that sufficient flatness cannot be obtained by straightening with a tension leveler. Since the duplex stainless steel according to one embodiment of the present invention has a hardness of 200 to 350 HV, the deformation resistance is not excessive, and a steel strip with excellent flatness can be obtained by passing through the straightening process.

[0059] (Mirror polishing process) The mirror polishing process is a process in which the steel strip surface after the straightening process is polished with a buff to give it a mirror finish. The method of polishing with a buff is not particularly limited, and any known method can be used. The abrasive grain size of the grindstone used for buffing can be selected arbitrarily. By carrying out the mirror polishing process, a mirror-finished duplex stainless steel with an arithmetic mean roughness (Ra) of the surface of 0.1 μm or less can be obtained.

[0060] In this mirror polishing process, if the hardness of the steel material to be subjected to the mirror polishing process is too high, the polishing load will be high and the consumption of the grindstone will also be large. The duplex stainless steel according to one embodiment of the present invention has a hardness of 200 to 350 HV, so the polishing load is not excessive and the polishing property is excellent.

[0061] As described above, in the manufacturing method of a mirror-finished duplex stainless steel according to one embodiment of the present invention, a duplex heat treatment is performed as a final annealing step, in which the cold-rolled steel sheet is heated to a temperature range (duplex temperature range) where the steel sheet is in a two-phase region of ferrite and austenite, and then cooled. In the process of the duplex heat treatment, at least a part of the carbides in the cold-rolled steel strip is taken into the austenite phase, and is cooled to be in a state of solid solution in the martensite phase. That is, the duplex heat treatment increases the amount of solute C in the martensite phase of the duplex stainless steel, and the martensite phase becomes hard. From this, it is considered that the amount of C solute in the martensite phase of the duplex stainless steel is reduced by shortening the holding time in the duplex temperature range. It is considered that the polishability and deformation workability of the duplex stainless steel are improved by reducing the hardness of the duplex stainless steel itself.

[0062] <Mirror-finished duplex stainless steel of the present invention> The mirror-finished duplex stainless steel according to one embodiment of the present invention obtained by the above-mentioned manufacturing method includes a ferrite phase and a martensite phase. The mirror-finished duplex stainless steel has a hardness of 200 to 350 HV, a waviness (arithmetic mean waviness: Wa) of 2.0 μm or less, and a surface roughness of 0.1 μm or less. In addition, in a cross section of the mirror-finished duplex stainless steel, the area ratio of the martensite phase is 60 to 80%, the area ratio of carbides is 0.5 to 2.0%, and the major axis of the carbides is 1 μm or less.

[0063] (Beneficial Effects) The duplex stainless steel obtained by the above-mentioned manufacturing method of the mirror-finished duplex stainless steel has excellent image clarity and scratch resistance. Moreover, the manufacturing method of the duplex stainless steel according to one embodiment of the present invention can obtain a duplex stainless steel having high strength and excellent deformation workability without performing additional heat treatment after the duplexing heat treatment. Furthermore, despite the high strength, the grinding load is low, so the consumption of grindstones is suppressed, and it is possible to manufacture the mirror-finished duplex stainless steel while reducing the possibility of an increase in manufacturing costs.

[0064] <Example> The results of evaluation of stainless steel sheets according to examples of the present invention (invention examples) and comparative examples will be described below.

[0065] Cold-rolled sheets having a thickness of 2.6 mm were prepared for stainless steels of steel types A to T having the chemical compositions shown in Table 1 below. Steel types A to M are steel types having compositions within the range of the present invention (hereinafter referred to as inventive steel types). Steel types N to T are steel types having compositions outside the range of the present invention (hereinafter referred to as comparative steel types). The underlined items in Table 1 are items outside the range of the chemical composition of the duplex stainless steel according to one embodiment of the present invention. The same is true for Table 2 below. [Table 1]

[0066] Next, the above steel types A to T were subjected to a final annealing process (multi-phase heat treatment), a straightening process, and a mirror polishing process under the conditions shown in Table 2 below. The annealing time in Table 2 means the soaking time at the multi-phase temperature. In Table 2, Nos. 1 to 13 are mirror-finished duplex stainless steels as examples of the present invention, in which the inventive steel types were subjected to a final annealing process under conditions within the range of the present invention. Nos. 14 to 18 are mirror-finished duplex stainless steels as comparative examples, in which the inventive steel types were subjected to a final annealing process under conditions outside the range of the present invention. Nos. 19 to 25 are mirror-finished duplex stainless steels as comparative examples, in which the comparative steel types were subjected to a final annealing process under conditions within the range of the present invention. The straightening process and mirror polishing process were performed in the same manner in all the examples and comparative examples. Table 2 also shows the results of evaluation of the martensite area ratio, carbide area ratio, carbide diameter (longer diameter of carbide), Vickers hardness, waviness, surface roughness, image clarity, and scratch resistance for the examples and comparative examples.

[0067] (Area ratio of martensite phase) The area ratio of the martensite phase in the cross section of each mirror-finished duplex stainless steel sheet obtained by performing the final annealing process, the straightening process, and the mirror polishing process under each condition was measured. For each steel sheet, the center of the thickness of the cross section parallel to the rolling direction and the plate thickness direction was photographed at 1000x using an optical microscope. The volume ratio of the martensite phase was calculated using the point counting method (JIS G0555) based on the photographed structure photographs. The results are shown in Table 2 under "Martensite area ratio (%)."

[0068] (Carbide area ratio) The area ratio of carbides in the cross section of mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process and the mirror polishing process under each set of conditions was measured. The center of the thickness of the cross section of each stainless steel sheet parallel to the rolling direction and the thickness direction was photographed at 2000x using a scanning electron microscope (SEM). The area ratio of carbides was calculated using the point counting method (JIS G0555) based on the backscattered electron images. The results are shown in Table 2 under "Carbide area ratio (%)."

[0069] (longest diameter of carbide) The long diameter of the carbides present in the mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process, and the mirror polishing process under each set of conditions was measured. The center of the sheet thickness of the cross section parallel to the rolling direction of each steel sheet was photographed at 2000x using an SEM. The long diameter of the largest carbide in the photographed backscattered electron image was measured, and the results are shown in Table 2 under "Carbide diameter (μm)."

[0070] (Vickers hardness) The Vickers hardness of each stainless steel sheet was measured using a Vickers hardness tester with a test load of 5 kg based on JIS Z2244 for the mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process and the mirror polishing process under each set of conditions. The evaluation results are shown in Table 2 under "Vickers hardness (HV)".

[0071] (undulation) The mirror-finished duplex stainless steel sheets obtained by the final annealing process, the straightening process and the mirror polishing process under each condition were measured for waviness (arithmetic mean waviness: Wa) according to JIS B0601. The measurement results are shown in Table 2 under "Waviness (μm)".

[0072] (Surface roughness) The arithmetic mean roughness (Ra) of the surface of the mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process and the mirror polishing process under each set of conditions was measured in accordance with JIS B0601. The measurement results are shown in the "Roughness (μm)" column of Table 2.

[0073] (Image clarity) The image clarity of the mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process and the mirror polishing process under each set of conditions was measured in accordance with JIS H8686. The measurement results are shown in Table 2 under "Image clarity (%)."

[0074] (Scratch resistance) The scratch resistance of the mirror-finished duplex stainless steel sheets obtained by carrying out the final annealing process, the straightening process, and the mirror polishing process under each condition was evaluated. The scratch resistance was evaluated by sliding a test needle with a load of 100 gf over the surface of the steel sheet and visually checking for the presence or absence of scratches. In Table 2, "◯" indicates that no scratches were visible and the scratch resistance was good. On the other hand, "×" indicates that scratches were visible and the scratch resistance was poor. [Table 2]

[0075] (About the results) The waviness and surface roughness are preferably small in terms of the surface quality of a mirror-finished product. In the present invention, a waviness of 2.0 μm or less and a surface roughness of 0.1 μm or less are considered as part of the conditions for the stainless steel of interest to be included within the technical scope of the present invention. In Table 2, Comparative Examples Nos. 14, 15, 17, 18, and 20 to 23 had a waviness of more than 2.0 μm and an arithmetic mean roughness of the surface of more than 0.1 μm, despite having been subjected to the same straightening treatment and mirror polishing treatment as the other Examples and Comparative Examples. This result is believed to be due to the fact that the deformation workability or polishability was reduced due to the high hardness. Inventive steel type In Examples Nos. 1 to 13, which were applied with the manufacturing method of the present invention, all had a waviness of 2.0 μm or less and an arithmetic mean roughness of the surface of less than 0.1 μm.

[0076] Moreover, as the surface quality of the mirror-finished product, the image clarity defined in JIS H8686 is preferably 85% or more. Therefore, for those with an image clarity of less than 85%, the results are considered to be poor, and the numerical values ​​are underlined. In Table 2, Comparative Examples Nos. 14, 15, 17, 18, and 20 to 23 had an image clarity of less than 85%, despite having been subjected to the same straightening treatment and mirror polishing treatment as the other Examples and Comparative Examples. This result is considered to be due to the waviness and surface roughness being outside the above-mentioned ranges. Example Nos. 1 to 13, in which the manufacturing method of the present invention was applied to the inventive steel, all had an image clarity of 85% or more, which was good.

[0077] In Table 2, Comparative Examples 16, 19, 24, and 25 had poor scratch resistance. This result is believed to be due to low hardness. Examples Nos. 1 to 13, in which the manufacturing method of the present invention was applied to the inventive steel, all had good scratch resistance.

[0078] As described above, in Examples 1 to 13 in which the inventive steel was processed according to the manufacturing method of the present invention, the martensite area ratio, carbide diameter, and Vickers hardness were within the ranges specified in the present invention.

[0079] On the other hand, in Comparative Examples 14 to 25, any one of the martensite area ratio, carbide diameter, and Vickers hardness was outside the range specified in the present invention. In Comparative Examples 16, 19, 24, and 25, the martensite area ratio was less than 60%. In other words, it is considered that the strength of the duplex stainless steel was not ensured.

[0080] As an example showing the effect of different annealing times, Example No. 9 of the present invention and Example No. 18 of the comparative example are compared. Example No. 9 of the present invention and Example No. 18 of the comparative example are the same steel type I and are subjected to the same multi-phase heat treatment at the same multi-phase temperature, but the annealing times are different. Since the multi-phase temperature is the same, the martensite area ratio of the two examples is the same, but the hardness of Example No. 18, which has an annealing time of more than 1 minute, is improved. This is thought to be because the carbide area ratio of Example No. 9 is 0.52%, while that of Example No. 18 is 0.31%, and therefore, in Example No. 31, more carbides are dissolved in the martensite phase, resulting in an increase in the hardness of the martensite phase.

[0081] (Effect of holding time at duplex temperature and duplex temperature on hardness of duplex stainless steel) 2 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the hardness of duplex stainless steel. The Vickers hardness (HV5) of the duplex stainless steel was measured when the holding time was 40 seconds and 90 seconds for a steel plate having the composition of the above steel type I and the duplexing temperature was changed between 900 and 1100°C. The HV5 value indicates the hardness measured using a Vickers hardness tester with a test load of 5 kg, as described above for the measurement of Vickers hardness. Regarding the holding time, 40 seconds is within the range of the present invention, and 90 seconds is outside the range of the present invention.

[0082] 2, when stainless steels having the same composition are subjected to the same duplexing temperature within the duplexing temperature range of the present invention (900 to 1100°C), the Vickers hardness is lower when the holding time at the duplexing temperature is 40 seconds. Also, when the holding time at the duplexing temperature is 90 seconds, the hardness is already about 350HV at a duplexing temperature of 1000°C.

[0083] This experiment demonstrated that within the duplexing temperature range of the present invention, duplex stainless steel having a hardness of 200 to 350 HV can be obtained by setting the holding time at the duplexing temperature to less than 1 minute.

[0084] (Effect of holding time at duplex temperature and duplex temperature on martensite area ratio) 3 is a graph showing the effect of the holding time at the duplexing temperature and the duplexing temperature on the martensite area fraction (M fraction) of duplex stainless steel. For a steel plate having the composition of steel type I, the holding time was 40 seconds and 90 seconds, and the duplexing temperature was changed between 900 and 1100°C, and the martensite area fraction was measured. The measurement of the martensite area fraction was carried out according to the method described above.

[0085] From Figure 3, it can be seen that the change in martensite area ratio with the change in the duplexing temperature shows a similar trend when the holding time at the duplexing temperature is 40 seconds and when it is 90 seconds. In other words, it has become clear that the martensite area ratio of duplex stainless steel is determined by the duplexing temperature, not by the holding time at the duplexing temperature.

[0086] [Additional Notes] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.

Claims

1. The composition contains, by mass%, 0.01 to 0.2% C, 0.01 to 2.0% Si, 0.1 to 4.0% Mn, 0.05% or less P, 0.03% or less S, 10 to 20% Cr, 0.01 to 4.0% Ni, 0.15% or less N, 0.01% or less O, with the balance being Fe and unavoidable impurities; Contains ferrite and martensite phases, Hardness is 200 to 350 HV, waviness is 2.0 μm or less, and the arithmetic mean roughness (Ra) of the surface is 0.1 μm or less; A mirror-finished duplex stainless steel sheet, in which in any cross section, the area ratio of the martensite phase is 60 to 80%, the area ratio of the carbides is 0.5 to 2.0%, and the major axis of each of the carbides is 1 μm or less.

2. The mirror-finished duplex stainless steel sheet according to claim 1, containing, by mass%, 4.0% or less of Cu.

3. 3. The mirror-finished duplex stainless steel sheet according to claim 1 or 2, containing, by mass%, at least one of 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM.

4. A final annealing step of heating to a temperature range of 800 to 1100 ° C. after the cold rolling step, soaking in the temperature range for less than 1 minute, and then cooling at a cooling rate of 1 ° C. / s or more; A straightening process by repeated stretching and bending; The method for producing a mirror-finished duplex stainless steel sheet according to claim 1, further comprising a mirror polishing step.

5. The method for producing a mirror-finished duplex stainless steel sheet according to claim 4, wherein the mirror-finished duplex stainless steel sheet contains 4.0% or less Cu by mass%.

6. The mirror-finished duplex stainless steel sheet contains, by mass%, at least one of 1.0% or less Mo, 1.0% or less W, 0.5% or less Co, 0.2% or less Al, 1.0% or less V, 1.0% or less Nb, 1.0% or less Ti, 0.005% or less B, 0.005% or less Ca, 0.005% or less Mg, 0.5% or less Sn, 0.5% or less Sb, 0.01% or less Ga, 0.01% or less Ta, 0.5% or less Zr, 0.1% or less Y, 0.01% or less Hf, and 0.1% or less REM. The manufacturing method of the mirror-finished duplex stainless steel sheet according to claim 4 or 5.

Citation Information

Patent Citations

  • High strength stainless steel thin sheet for id blade and its production

    JP1995258733A

  • Aperture frame using double layer stainless steel stock

    JP1997249942A

  • Mirror-finished dual-phase stainless steel sheet excellent in scratch resistance, and its production

    JP1999152550A

  • Manufacture of ferritic stainless steel sheet excellent in surface characteristic and ridging resistance

    JP1999209826A

  • Chromium based stainless steel, and production method therefor

    JP2004244691A